Bilateral oral lichenoid lesions on the buccal mucosa due to methotrexate: Report of two cases. Issue 1 (January 2015) - Jinbu, Yoshinori; Kashiwazaki, Akiko; Ozawa, Michiko; Inoue, Emi; Kusama, Mikio; Demitsu, Toshio
Abstract Lichenoid drug eruptions have been previously reported. Here, we report two cases of bilateral oral lichenoid lesions on the buccal mucosa that appeared during low-dose methotrexate treatment for rheumatoid arthritis. The first case was a 71-year-old woman on methotrexate for rheumatoid arthritis, who presented with bilateral oral ulceration on the buccal mucosa. On examination, erythematous ulcers surrounded by white plaques and striae were seen. Oral lichen planus was suspected clinically but topical steroids were ineffective. However, an improvement was observed after reducing the dose of methotrexate, and epithelialization occurred after drug cessation. Reintroduction of methotrexate resulted in recurrence. Histopathological examination of a biopsy taken from the oral mucosa confirmed the lesion as an oral lichenoid lesion. The second case was an 87-year-old woman on methotrexate for rheumatoid arthritis, who presented with pain of the oral mucosa. On examination, ulceration, erythema, and white plaques were observed bilaterally on the buccal mucosa. The disease was diagnosed clinically as oral lichen planus but no improvement was seen after topical steroid treatment. The lesions disappeared after discontinuation of methotrexate. This is the first report of oral lichenoid lesions due to methotrexate.